Efforts to Increase Student Motivation and Activeness by Using The Zoom Application in SDN 4 Samudra - Lestari, Rini (Universitas Sebelas Maret, 2020)
This study aims to determine to what extent the use of the Zoom application in online learning can increase student motivation and activeness in thematic learning theme 4 for grade 3 SDN 4 Samudra. This research was conducted through a cycled assessment process (Classroom Action Research) which included four stages, namely planning (planning), acting, observing (observing) and reflecting (reflexing). Motivation and activeness data were taken from observation sheets during the learning process and self-assessment sheets by students and teachers. The data analysis in this research used quantitative and descriptive qualitative. From the results of data analysis, the following conclusions were obtained: (1) The use of the Zoom application in thematic online learning for grade 3 semester 1 SDN 4 Samudra in the 2020/2021 academic year was able to increase student motivation and activeness, (2) There was a positive correlation between motivation and activeness student learning, the more motivated to take part in online learning, the more active students are in learning.